PEMANFAATAN LIMBAH HASIL PENGUJIAN BETON PADA PROYEK BYPASS (BIL) MANDALIKA SEBAGAI PENGGANTI SEBAGIAN AGREGAT KASAR BETON NORMAL - Dewi, Evrianti (Jurnal Handasah, 2023)
ABSTRACT Concrete waste is one of the wastes that is rarely used and is piling up along with the increasing construction and renovation of buildings. Penujak village, located in Central Lombok, produces concrete waste which is the result of a compression cylinder concrete test for the construction of the BIL Mandalika Bypass road. The BIL Mandalka Bypass line has 4 lanes with a length of 17,363 km. The concrete waste if not utilized can be a source of environmental pollution. In this study, the researchers utilized concrete waste from the compression test results in the construction of the Mandalika BIL Bypass to replace some of the coarse aggregate. Cylindrical specimens with a diameter of 15 cm and a height of 30 cm were used as samples for compression testing, with a mix design concrete quality of 30 MPa. The variation in the percentage of partial replacement of coarse aggregate with waste concrete used in this study was 15%, 29%, 25% and 30%, respectively. The standard procedure for making normal concrete mix plans refers to SNI 03-2834-2000 The test results show that the compressive strength increases at the replacement of 20% of the coarse aggregate with waste concrete. The compressive strength value obtained is 31.29 MPa. The compressive strength decreases along with the increase in the percentage of replacement of coarse aggregate with waste concrete. At the addition of 30% of waste concrete the compressive strength decreases to 25.55 Mpa